Metacognitive Theory-Based Learning Video to Improve Learning Outcomes in Pancasila Subjects for Fifth-Grade Elementary School Students - Ni Ketut Virna Jayanti; I Kadek Suartama; Alexander Hamonangan Simamora (Universitas Pendidikan Ganesha, 2025)
The background of this study is the problem faced by students regarding Pancasila material, which is insufficiently visualized through the use of technology. This study aims to develop learning video media for Pancasila lessons. The type of research is developmental, using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects included 1 content learning expert, 1 instructional design expert, 1 learning media expert, 3 students in individual trials, and 9 students in small-group trials. Data collection methods employed were questionnaires, observation, interviews, written tests, and document recording, using instruments such as questionnaires, observation sheets, interview guides, and test items. Data analysis was conducted using quantitative descriptive statistics and inferential statistics (correlated t-test). The results showed that the learning media received high validation scores from the experts: 95% from the content expert, 92% from the design expert, and 96% from the media expert, all classified as very good; individual trials with three students achieved an average score of 89.23% (good), while small-group trials with nine students achieved an average score of 91.96% (very good). The implications of this study indicate positive impacts for school principals, teachers, and students, supporting a more effective, interactive learning process that enhances student engagement and understanding optimally.